Technology and Engineering Literacy Profile of High School Students: Comparison between STEM and Non-STEM Learning - Sumiati, Sumiati; Suwarma, Irma Rahma; Utama, Judhistira Aria; Riandi, Riandi; Kuroda, Tomotaka (FKIP Universitas Lampung, 2025)
Technology Engineering Literacy (TEL) represents an essential competency in the 21st century, encompassing the ability to understand, evaluate, and apply technological and engineering concepts in everyday life and professional settings. This study was conducted to compare the TEL profiles of high school students engaged in Science, Technology, Engineering, and Mathematics (STEM) and non-STEM fields, with a particular emphasis on the renewable energy topic. The research employed a quantitative approach and involved 125 high school students, who were selected by purposive sampling techniques. Data were collected utilizing a TEL test instrument specifically designed for this research. Mann-Whitney analysis using SPSS 26 revealed a significant difference between STEM and non-STEM groups. Additionally, the TEL profiles of STEM and non-STEM students were evaluated by examining the percentages of complete and incomplete achievements. The findings show that students participating in STEM learning demonstrated a superior TEL profile compared to their non-STEM peers. Specifically, regarding the understanding of technological principles, 89% of STEM students completed the assessment, whereas only 75% of non-STEM students achieved this. In the context of developing solutions and reaching goals, 84% of STEM students met the completion criteria, in contrast to 63% of non-STEM students. For the technology and society dimension, 87% of STEM students completed the assessment, compared to only 59% of non-STEM students. In the design and systems area, 89% of STEM students completed the tasks, while 81% of non-STEM students did. Lastly, in the Information and Communication Technology (ICT) domain, 82% of STEM students reached the completion category, while merely 60% of non-STEM students did. These results emphasize the significant impact of STEM learning in enhancing students’ technology engineering literacy, thereby equipping students with essential skills relevant to the needs of the 21st century. Keywords: technology_and_engineering_literacy, STEM, renewable_energy.